Criminal Liability for Misuse of Electronic Medical Records in Health Services - Prilian Cahyani; Astutik Astutik (Universitas Katolik Soegijapranata Semarang, 2019)
Electronic medical records (RME) have been used in hospitals as a substitute for or complementary to medical records in the form of paper. The obligation to make medical records is the responsibility of every doctor or dentist in carrying out the medical practice. However, the use of electronic-based medical records does not rule out the possibility of raising problems in the field of law, if some abuse it. This will raise the issue of who has the obligation to take responsibility. The problem is the background of the author to write in an article with the title